Stable difference scheme for a nonlinear Klein-Gordon equation - Nizhnik, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For a nonlinear Klein-Gordon equation, we obtain a stable difference scheme for large time intervals. We prove that this scheme has the sixth order of accuracy.